Vitamin A effects and requirements on the juvenile Kuruma Prawn Marsupenaeus japonicus - Hernandez Hernandez, Luis Héctor; Shin-Ichi, Teshima; Ishikawa, Manabu; Koshio, Shunsuke; Gallardo-Cigarroa, Francisco Javier; Uyan, Orhan; Alam, Md. Shah (HIDROBIOLÓGICA, 2017)
A 40-day feeding experiment was conducted to assess the effect and requirements of dietary vitamin A (vitA) of juvenile Kuruma Prawn Marsupenaenus japonicus. Nine semi-purified diets were prepared with supplementations of 0, 3,000, 6,000, 9,000, 12,000, 15,000, 18,000, 21,000 and 24,000 international units of vitA per kg (IU vitA/kg) and fed once a day to triplicate groups of 15 juveniles per tank (initial weight of 0.14 ± 0.001 g, mean ± standard error). Weight gain (WG), specific growth rate (SGR) and feeding efficiency ratio (FER) were significantly lower in the juveniles fed with the diets contained 0 and 3,000 IU vitA/kg than in the other groups. Similar values of total retinol (ROL) in whole body were detected only in the juveniles fed on the diets supplemented with 21,000 and 24,000 IU vitA/kg: 10.22 ± 2.74 and 10.70 ± 0.14 ?g ROL /g of wet weight, respectively (mean ± standard error). It was not possible to detect retinal in the whole body samples in any of the experimental groups. According to the WG analyzed by the broken line regression, the dietary requirements of vitA should be of 7,500 IU vitA/kg.